A Case of Cryptococcus gattii in Western Florida. Issue 2 (March 2015) - Tiro, Aileen V.; Springer, Deborah J.; Irby, Rachel; Averill, Francis; Ottaviani, Anthony; Heitman, Joseph; Perfect, John R.
<x xml:space="preserve">Abstract</x> Background Cryptococcus gattii is an environmental pathogenic yeast that produces disease in the skin, the respiratory tract, and the central nervous system of both immunocompromised and immunocompetent hosts. The incidence of C. gattii disease is increasing in frequency and, importantly, appears to be spreading its geographic clinical appearance since the first identified case series, which had shown defined boundaries. Case A 56-year-old previously healthy woman presented for medical care with 3 weeks of progressive weakness, headache, neck pain, and back pain. Initial computed tomographic scan results of the head and the spine were normal. However, chest x-ray showed a large right upper lobe mass. Bronchoscopic examination revealed a partially obstructing endobronchial polyp, on which a biopsy was performed, and culture of the tissue grew encapsulated yeast cells. Magnetic resonance imaging of the brain revealed multiple rim-enhancing lesions, and cerebrospinal fluid grew encapsulated yeasts that were identified as C. gattii, molecular-type VGI. Conclusions This is a virulent VGI strain of C. gattii, causing infection in an immunocompetent host in Western Florida with no recent travel history. Here, we discuss clinical, laboratory, diagnostic, and pathologic findings of the clinical presentation and its delayed diagnostic appearance in a nonendemic area.